The Effect of Brainwriting Learning Model Assisted by Short Film Media Bullying “RAPUH” on the Ability of Writing Response Texts of Grade VII Students of SMP Negeri 2 Percut Sei Tuan - Fika Salsabila Amar; Azhar Umar (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study aims to analyze whether there is an effect of using the Brainwriting model assisted by the short film media bullying "Rapuh" on the ability to write response texts of class VII students of SMP Negeri 2 Percut Sei Tuan. The population in this study were students of class VII of SMP Negeri 2 Percut Sei Tuan with a sample size of 34 students in the first class and 34 students in the second class. The instruments used in this study were context, description, assessment, responses agreeing to opinions, responses rejecting opinions and responses to suggestions. The method used in this study was the Two Group Posttest design. The data analysis technique used the analysis prerequisite test, namely the normality test, homogeneity test, and hypothesis test. The results of the study in the control class obtained an average value of 64.62 and was categorized as sufficient. Meanwhile, the results of the experimental class research obtained an average value of 86.38 and included in the Very Good category. through hypothesis testing, namely t table count, namely 10.705 > 1.69092, it can be concluded that there is a significant influence of the use of the Brainwriting model assisted by the short film media bullying "Rapuh" on the ability to write review texts of class VII students of SMP Negeri 2 Percut Sei Tuan.